Impact of Swollen Shoot Disease on the Livelihoods of Smallholder Cocoa Farmers in Côte d’Ivoire - Adopo, Wenceslas Affessi; Adolphe, Mahyao Germain; Tiehi, Nestor; Koffi, Camille; Kouakou, Koffie; Ballo, Zié (European Scientific Journal, ESJ, 2022)
Cocoa Swollen Shoot Disease (CSSD) due to badnavirus species is endemic in West Africa and has been causing significant and irreversible economy losses for smallholder cocoa farmers in infected areas in Ghana and Côte d’Ivoire. The impact of the disease on the smallholder farmers’ livelihoods has been investigated at cocoa farm households level in Côte d’Ivoire. To this end, the propensity score matching method was used to construct a counterfactual and to compare groups capturing the situation of affected households before the disease affects their plantations, based on the observable characteristics of non affected households. A total of 800 cocoa farmers were randomly interviewed using a semi-structured questionnaire. The results showed significant differences in expenditures for children’s schooling and health between households with plantations infected by the disease and those with non-infected plantations. It was also found that households with swollen shoot in their cocoa plantation used less modern health services and invested less in children’s education. The results imply that swollen shoot control policies and strategies should take into account socioeconomic factors.